Development of a gait training device for children with cerebral palsy - BENNETT, GARETH; O'DONNELL, GARRET EDWARD; SIMMS, CIARAN KNUT (My University, 2010)
Children with Cerebral Palsy (CP) can generally not walk unaided, but do have some weight bearing ability. Therefore walking aids are often more appropriate than wheelchairs, see figure 1. These devices facilitate mobility and also provide vital mechanical stimulation of the lower limbs [1]. However, existing designs show little evidence of being optimized for ergonomics and biomechanical function, let alone aesthetics. A current collaboration between Moorings Mediquip (Northern Ireland) and Trinity College Dublin funded by an Intertrade Ireland Fusion grant is concerned with developing a new gait trainer for children with CP which has improved functionality and aesthetic features compared to existing products.
TCD-UCD Engineering Design Innovation Research Event
PUBLISHED
Keywords: Bioengineering; Design; Medical Devices; Gait Trainer